Faculty and Student Perspectives on Mentorship in a Nursing Honors Program. Issue 1 (January 2018) - Nelson, Noreen; Lim, Fidelindo; Navarra, Ann-Margaret; Rodriguez, Karla; Witkoski Stimpfel, Amy; Slater, Larry Z.
Abstract : Abstract: Honors programs in nursing can facilitate the professional development of high-achieving students, supporting their lifelong engagement in nursing practice, education, research, and health care policy issues. Strong mentoring relationships are commonly identified as essential to the success of nursing honors programs, but literature on mentoring relationships in an honors context is limited. The purpose of this study was to gain insight into faculty and student expectations for mentorship. Faculty and students shared similar expectations for both the mentor and mentee, highlighting key themes of engagement, facilitation, accountability, and collaboration as necessary for the success of an undergraduate nursing honors program.